2019
DOI: 10.1002/cncr.32200
|View full text |Cite
|
Sign up to set email alerts
|

Race and risk of subsequent aggressive breast cancer following ductal carcinoma in situ

Abstract: Background General populations of black women have a higher risk of developing breast cancer negative for both estrogen receptor (ER) and progesterone receptor (PR) in comparison with white counterparts. Racial differences remain unknown in the risk of developing aggressive invasive breast cancer (IBC) that is characterized by negativity for both ER and PR (ER–PR–) or higher 21‐gene recurrence scores after ductal carcinoma in situ (DCIS). Methods This study identified 163,892 women (10.5% black, 9.8% Asian, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 41 publications
3
21
1
Order By: Relevance
“…Although the performance was impressive, certain caveats should be taken into account when considering how generalized this model might be. Given the complexity of breast cancer subtypes and the impact of patient demographics on outcome (Alaeikhanehshir et al, 2020;Liu et al, 2019), the sample size in this study may not have been sufficient to fully account for the confounding effects of these variables. Lastly, since all patients in the RAHBT cohort received one or more therapeutic interventions, the features leveraged by this model to identify non-progressors might not be valid when applied to patient populations where therapy is omitted.…”
Section: Discussionmentioning
confidence: 99%
“…Although the performance was impressive, certain caveats should be taken into account when considering how generalized this model might be. Given the complexity of breast cancer subtypes and the impact of patient demographics on outcome (Alaeikhanehshir et al, 2020;Liu et al, 2019), the sample size in this study may not have been sufficient to fully account for the confounding effects of these variables. Lastly, since all patients in the RAHBT cohort received one or more therapeutic interventions, the features leveraged by this model to identify non-progressors might not be valid when applied to patient populations where therapy is omitted.…”
Section: Discussionmentioning
confidence: 99%
“…In a nationally representative population of DCIS patients diagnosed between 1990 and 2015, we demonstrated that compared with white women, the risk of developing ER−PR− invasive breast cancer was significantly increased by 86% (HR = 1.86, 95% CI 1.57–2.20) in black women and by 40% in Asian women (HR = 1.40, 95% CI 1.14–1.71). The associations for ER−/PR− invasive cancer were stronger than the associations for ER+/PR+ subtypes (HR = 1.31, 95% CI 1.21–1.43 in blacks; HR = 1.01, 95% CI 0.92–1.11 in Asians; H eterogeneity = 0.0004) [24]. Thus, the magnitude of the associations between black race and risk of invasive breast cancer subtypes following LCIS and DCIS was similar.…”
Section: Discussionmentioning
confidence: 99%
“…Racial differences in breast cancer diagnosis, prognosis, and survival are well documented 4‐10 . However, these studies typically aggregate women from geographically diverse countries in East Asia, Southeast Asia, and the Indian subcontinent into a single Asian racial group.…”
Section: Introductionmentioning
confidence: 99%